Analysis of Achaemenian Art and Architecture with Reference to Origins, Influences, and Development. Ph. D. Vol. II - Katrаk, Verā Sohrab (2000)
M. E. L. Mallowan; Typescript; Part II: 8. Art; 9. Early Iranian tomb reliefs; 10. Sculptured reliefs from Pasargadae Palaces; 11. Rock reliefs at Behistun and Naqsh-i-Rustam; 12. Guardian bull colossi at Persepolis; 13. The King enthroned; 14. Reliefs from the Apadana at Persepolis; 15. Reliefs from the palace of Darius I. at Persepolis; Part III: Minor arts and crafts; 18. Jewellery; 19. Decorated bowls; 20. Miscellanea.